Hubungan Antara Kepemimpinan Transformasional Kepala Sekolah terhadap Motivasi Kerja Guru di SMP Negeri 3 Langkat - Muhammad Irvan Marsya; Candra Wijaya; Fathur Rohman (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The principal's leadership is one of the important components that determines the growth and sustainability of educational institutions. School principals have a great opportunity to develop leadership values ​​in the modern era. To develop education, high-quality and continuously developing leaders are needed. In addition, school principals must motivate teachers because they have to make a major contribution in the educational environment. This research was conducted using quantitative methods with a correlational type. This research used a total sampling technique, with a total sample of thirty teachers and academic staff. This research instrument consists of thirty questionnaires, or questionnaires, for each variable. The research results show that the correlation coefficient between the principal's transformational leadership variable (X) and teachers' work motivation (Y) is 0.623, thus the relationship between the two is quite strong.